(untitled) (Construction Economics and Building, 2018)
Adoption of Building Information Modelling (BIM) in the global construction industry is fast growing. This paper expounds the Critical Success Factors (CSFs) for BIM implementation and explore their ranking and underlying relationships. A total of 28 CSFs was identified from the review of previous studies on success factors. Survey questionnaire containing these 28 factors was used to collect data from industry practitioners in Nigeria. Benchmark metrics was developed to rank the success factors. The topmost five success factors for BIM implementation in order of importance are: standard platforms for integration and communication; cost of development; education and training; standardization (product and process); and clear definition and understanding of users’ requirement. Analysis of variance shows that significant differences exist in the pattern of rating for the topmost CSFs based on turnover. Factor analysis was further adopted to group the 28 CSFs into five components, using rotated component matrix method. The five components extracted are: (i) industry stakeholders’ commitment and knowledge of BIM, (ii) capacity building for technology adoption, (iii) organisational support, (iv) collaborative synergy among industry professional and (v) cultural orientation. The rankings of the CSFs provide basis for prioritising the most significant factors that industry stakeholders should focus attention for successful implementation of BIM. In addition, the underlying relationships among the success factors identified in this study, will assist industry stakeholders to determine best strategy to adopt in implementing BIM at industry level.